UNVEILING THE UNIVERSITY STUDENTS' MOTIVE OF USING TABOO WORDS IN DAILY CONVERSATION - Frida Ukhtinabila; Masriatus Sholikhah (JEELL (Journal of English Education, Linguistics and Literature), 2026)
This study was conducted at three private universities in East Java: one non-religious campus and two religious-based campuses. This research aims to explore the reasons behind the use of taboo words in daily conversations among university students.  A descriptive qualitative method was employed, using questionnaires and interviews as data collection tools.  The data sources for this study included online questionnaires and interviews with several students. The data were analyzed based on Battistella’s (2005) classification of taboo words and Jay’s (2009) Theory. The findings reveal that the primary reasons for using taboo words were to express emotions, strengthen social bonds among close friends, add humor, and react spontaneously to certain situations. This research indicates that students tend to use taboo words deliberately and contextually, mainly in social settings where they feel comfortable and free from formal constraints. Frequent exposure to social media and peer influence significantly contributes to the development of this linguistic behavior in students’ everyday communication